2021
DOI: 10.1038/s41438-021-00567-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of SlARC6 leads to tissue-specific defects in chloroplast development in tomato

Abstract: The proliferation and development of chloroplasts are important for maintaining the normal chloroplast population in plant tissues. Most studies have focused on chloroplast maintenance in leaves. In this study, we identified a spontaneous mutation in a tomato mutant named suffulta (su), in which the stems appeared albinic while the leaves remained normal. Map-based cloning showed that Su encodes a DnaJ heat shock protein that is a homolog of the Arabidopsis gene AtARC6, which is involved in chloroplast divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…NAL11 may be involved in chloroplast development and extensively modulate GA homeostasis NARROW LEAF 11 is an HSP with a DnaJ domain (J protein) from the family the molecular chaperones widely present in plants (Georgopoulos et al, 1979;Waters, 2013). The reported J proteins are primarily localized in chloroplasts and affect chloroplast development, photosynthesis, protein transport, and other processes (Vitha et al, 2003;Chen et al, 2010;Chang et al, 2021). The chloroplast is also the major organelle in which NAL11 is mainly localized (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NAL11 may be involved in chloroplast development and extensively modulate GA homeostasis NARROW LEAF 11 is an HSP with a DnaJ domain (J protein) from the family the molecular chaperones widely present in plants (Georgopoulos et al, 1979;Waters, 2013). The reported J proteins are primarily localized in chloroplasts and affect chloroplast development, photosynthesis, protein transport, and other processes (Vitha et al, 2003;Chen et al, 2010;Chang et al, 2021). The chloroplast is also the major organelle in which NAL11 is mainly localized (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Plant Science 13 frontiersin.org 2022), (Schultes et 1996), tomato (Solanum lycopersicon; Chang et al, 2021), and wheat (Triticum aestivum; Li et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Normally, chloroplasts are found in plants, algae, and protozoa. However, leaf color mutations are associated with chloroplast structural variations in several plants, including rice ( Chen et al, 2018 ), Arabidopsis ( Song et al, 2004 ), tobacco ( Bae et al, 2001 ), pepper ( Capsicum annuum ; Shi et al, 2022 ), maize ( Schultes et al, 1996 ), tomato ( Solanum lycopersicon ; Chang et al, 2021 ), and wheat ( Triticum aestivum ; Li et al, 2013 ). In this study, the chlorophyll a, chlorophyll b, and carotenoid contents of the mutants were significantly reduced, but the pigment composition was consistent with that of the WT.…”
Section: Discussionmentioning
confidence: 99%
“…These kinds of PPRs involved in chloroplast development have been found in other species, including DG1 ( Chi et al, 2008 ) and YS1 ( Zhou et al, 2010 ) in Arabidopsis , and PPR4 ( Schmitz-Linneweber et al, 2006 ) and PPR10 ( Prikryl et al, 2011 ) in maize. As a tissue-specific albino, a tomato mutant suffulta (su) with albinic stems and visually normal leaves were collected ( Chang et al, 2021 ). Map-based cloning showed that Su encodes a DnaJ heat shock protein, and the homolog gene AtARC6 (accumulation and replication of chloroplasts) in Arabidopsis is involved in chloroplast division.…”
Section: Discussionmentioning
confidence: 99%
“…A two-step mutation process in the double White Stem 1 homologs has driven the evolution of burley tobacco (Wu et al, 2020). A similar phenotype was identified from a tomato mutant with albinic stems and this is caused by a mutation of SlARC6, which leads to the tissue-specific defects in chloroplast development (Chang et al, 2021).…”
Section: Introductionmentioning
confidence: 88%